World perceptions of racism in Australia - Australia. Office of the Commissioner for Community Relations (Canberra : Office of the Commissioner for Community Relations, Australia, 1981)
Examines overseas knowledge of, and reactions to, racism in Australia, with many references.
Cover title.
Includes bibliographical references.
Keywords: Race relations. Australia; Sport - Commonwealth Games; Race relations - Racism; Australia -- Race relations